PENGUKURAN PRODUKTIVITAS TOTAL DENGAN METODE RASIO OUTPUT INPUT DI CV. AGRINDO SUPRAFOOD - , ASEPTY ARIE RISKY, Ir. Suharno, M.Eng M.Eng.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Measurement of total productivity in CV. Agrindo Suprafood conducted to determine how the total productivity in the industry from March 2013 until April 2013 and the factors that affect the total productivity improvement . The method used to accomplish this final method is to use the input output ratio . To calculate the total productivity of each month the total output produced in a given month divided by the total inputs used in the same month , the results of this calculation will be analyzed in a way comparable to the total productivity in the following months and the moon base to be used is the benchmark in comparing the month of March 2013 . Based on the measurement results show that the total productivity always increase when compared to the base month ( March 2013 ) . The most substantial increases occurred in April 2013. Increase was influenced by the number of products sold in April 2013 , where the products sold are selling a product that has a higher value . More and more products with high sales value sold , then the output will be obtained will also be greater .